The Norseman's song - Deane, Joel (Hunter Melbourne, 2010)
An outstanding Australian literary mystery. An ancient man with no past hails a taxi driven by a petty crim with no future. Reluctantly the pair embarks on a journey in search of a legendary whaler and murderer known only as The Norseman